2020
DOI: 10.1038/s41467-020-18255-5
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation study of Huntington’s disease and motor progression in patients and in animal models

Abstract: Although Huntington’s disease (HD) is a well studied Mendelian genetic disorder, less is known about its associated epigenetic changes. Here, we characterize DNA methylation levels in six different tissues from 3 species: a mouse huntingtin (Htt) gene knock-in model, a transgenic HTT sheep model, and humans. Our epigenome-wide association study (EWAS) of human blood reveals that HD mutation status is significantly (p < 10−7) associated with 33 CpG sites, including the HTT gene (p = 6.5 × 10−26). These Htt/H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 60 publications
2
43
0
1
Order By: Relevance
“…The polyglutamine expansion in the HTT protein is an indicator of early stage HD. Drastic changes in DNA methylation has been found associated with this expansion and that increased mHTT expression; resulting in declined neurogenesis, cognition, and motor function in transgenic mouse and human (Ng et al, 2013;Lu et al, 2020).…”
Section: Huntington's Diseasementioning
confidence: 99%
“…The polyglutamine expansion in the HTT protein is an indicator of early stage HD. Drastic changes in DNA methylation has been found associated with this expansion and that increased mHTT expression; resulting in declined neurogenesis, cognition, and motor function in transgenic mouse and human (Ng et al, 2013;Lu et al, 2020).…”
Section: Huntington's Diseasementioning
confidence: 99%
“…Similar to AD and PD, HD also exhibits an accelerated epigenetic age. Only the CpGs located in proximity (within 2 kb) to the CAG expansion in exon 1 of HTT are significantly hypermethylated in HD, which exhibit positive correlations with severe motor progression in patients [ 164 , 165 ]. Amyotrophic lateral sclerosis (ALS) is the most common neurodegenerative disease of the motor neuron system, which is generally caused by mutations in the chromosome 9 open reading frame ( C9orf72 ) gene [ 166 ].…”
Section: Epigenetic Modulation To Reverse Motor Deficitsmentioning
confidence: 99%
“…The human epigenome shows characteristic changes during the aging process and based on altered DNA methylation patterns an epigenetic age can be calculated [ 38 ]. As HD is an age-dependent, progressive disorder several of the above detailed genome-wide DNA methylation studies asked whether mHtt induced pathogenesis alters epigenetic age [ 33 , 36 , 37 ]. Genome-wide CpG methylation analysis of 475 tissue samples from nine brain regions (Frontal lobe, Occipital lobe, Parietal lobe, Temporal lobe, Caudate nucleus, Cerebellum, Cingulate gyrus, Hippocampus, and Midbrain) indicated that epigenetic age is altered in HD in general, and this effect depended on the clinical severity of the disease: HD cases without the most severe Vonsattel (VS) grade 4 [ 39 ] samples showed a significant epigenetic age acceleration effect in the parietal and frontal lobes and the cingulate gyrus, increasing biological age by several years.…”
Section: Lessons From Genome-wide Dna Methylation Studiesmentioning
confidence: 99%
“…Furthermore, epigenetic age acceleration showed a positive correlation with age of motor onset, but a negative correlation with CAG repeat length, the latter effect is most likely related to the decelerated epigenetic aging in VS grade 4 samples that had the longest CAG repeats in the study [ 33 ]. Similarly, significant epigenetic age acceleration was shown in manifest HD cases compared to controls by analyzing blood samples from the Enroll-HD and Registry-HD studies, and epigenetic age acceleration showed positively correlated with the progression of motor symptoms [ 36 ]. In contrast to the findings above no significant differences in DNA methylation age between human HD and control forebrain cortical samples were found by De Sousa et al in a smaller sample set [ 17 ].…”
Section: Lessons From Genome-wide Dna Methylation Studiesmentioning
confidence: 99%
See 1 more Smart Citation